Bicyclic Guanidine Catalyzed Asymmetric Tandem Isomerization Intramolecular‐Diels–Alder Reaction: The First Catalytic Enantioselective Total Synthesis of (+)‐alpha‐Yohimbine. Issue 3 (12th June 2015) - Feng, Wei; Jiang, Danfeng; Kee, Choon‐Wee; Liu, Hongjun; Tan, Choon‐Hong
Abstract: Hydroisoquinoline derivatives were prepared in moderate to good enantioselectivities via a bicyclic guanidine‐catalyzed tandem isomerization intramolecular‐Diels–Alder (IMDA) reaction of alkynes. With this synthetic method, the first enantioselective synthesis of (+)‐alpha‐yohimbine was completed in 9 steps from the IMDA products. Abstract : Tandem cycling : A bicyclic guanidine‐catalyzed asymmetric tandem isomerization intramolecular‐Diels–Alder reaction is reported to achieve the first catalytic enantioselective total synthesis of (+)‐alpha‐yohimbine.